2015
DOI: 10.1111/hel.12285
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Five Different Treatment Regimens as the First‐Line Treatment of Helicobacter pylori in Turkey

Abstract: Bismuth-enhanced sequential therapy can be recommended to overcome resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…One from China found significantly superior eradication rates for a modified bismuth‐based therapy with rabeprazole, levofloxacin, and clarithromycin (91.7% vs 74.4%) . Another study from Turkey looked at a ST regimen enhanced with bismuth and looked at it on a retrospective basis in comparison with bismuth‐based quadruple treatment, ST with clarithromycin, ST with levofloxacin, and hybrid treatment, and found significantly better eradication (88.5%) in the bismuth‐enhanced ST group . A similar study also conducted in Turkey comparing conventional and ST with four other regimens found both concomitant and ST to be an effective treatment for H. pylori with bismuth‐based quadruple therapy and standard triple therapies being ineffective for eradication …”
Section: Sequential Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…One from China found significantly superior eradication rates for a modified bismuth‐based therapy with rabeprazole, levofloxacin, and clarithromycin (91.7% vs 74.4%) . Another study from Turkey looked at a ST regimen enhanced with bismuth and looked at it on a retrospective basis in comparison with bismuth‐based quadruple treatment, ST with clarithromycin, ST with levofloxacin, and hybrid treatment, and found significantly better eradication (88.5%) in the bismuth‐enhanced ST group . A similar study also conducted in Turkey comparing conventional and ST with four other regimens found both concomitant and ST to be an effective treatment for H. pylori with bismuth‐based quadruple therapy and standard triple therapies being ineffective for eradication …”
Section: Sequential Therapymentioning
confidence: 95%
“…For example, studies were combined without subanalyzing data from different lengths of concomitant treatment and several of the comparisons that were made could be considered unequal in that treatment arms had different lengths of treatment. The adverse events and adherence to medications were not different between the two regimens in this meta-analysis.A number of other studies compared ST to bismuth-based quadru-and found significantly better eradication (88.5%) in the bismuth-enhanced ST group 37. A similar study also conducted in Turkey comparing conventional and ST with four other regimens found both concomitant and ST to be an effective treatment for H. pylori with bismuth-based quadruple therapy and standard triple therapies being ineffective for eradication 38.…”
mentioning
confidence: 95%
“…The H. pylori eradication strategy is based on a combination therapy of antibiotics and acid suppressants, i.e., proton pump inhibitors (PPIs). The choice of an antibiotic depends on several factors, namely local resistance profiles, prior antibiotic therapy, history of allergy to specific antibiotics, patient age, renal and hepatic function and comorbid conditions, drug costs, adverse effects, and ease of administration [ 7 , 8 ]. Due to the growing increase in antibiotic resistance, the efficacy of antimicrobials in eradicating H. pylori infection has significantly decreased.…”
Section: Introductionmentioning
confidence: 99%